Pengaruh Word Of Mouth (Wom) Dan Brand Loyalti Terhadap Minat Beli Konsumen (Studi Kasus Pada Distributor Sparepart Motor Ud. Berkat Mulia) - Fitri, Septa Yunanda; ., Trisninawati; Helmi, Sulaiman; Roni, Mukran (CV. ITTC INDONESIA, 2025)
This research is motivated by the problems faced by UD. Berkat Mulia, namely the increasing number of motorcycle spare part stores, intense competition, the presence of brand loyalty among consumers, and consumers who are sensitive to services that must be as good as possible because it can affect the results received by consumers. If the service is not satisfying, there will be bad testimonials which will be heard by the outside community, and this will have a negative impact in the future on consumer purchase intention. This study aims to analyze the influence of brand loyalty on word of mouth and consumer purchase intention, as well as to determine the mediating role of word of mouth in the relationship between brand loyalty and purchase intention at UD. Berkat Mulia. The research method used is quantitative with a Structural Equation Modeling Partial Least Square (SEM-PLS) approach. The research sample consisted of 100 respondents selected using the Slovin technique. The results show that brand loyalty has a positive and significant effect on word of mouth, and also has a positive and significant effect on purchase intention. In addition, word of mouth is also proven to have a positive and significant effect on purchase intention. Another finding indicates that word of mouth is able to mediate the effect of brand loyalty on consumer purchase intention. Thus, this research emphasizes the importance of strengthening brand loyalty in increasing consumer recommendations and encouraging purchase intention. Practically, the results of this research can be used as a reference for companies in formulating more effective marketing strategies through optimizing brand loyalty and the dissemination of positive word of mouth.